2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin (TCDD) induces hepatic stellate cell (HSC) activation and liver fibrosis in C57BL6 mouse via activating Akt and NF-κB signaling pathways. (5th May 2017) - Han, Ming; Liu, Xipeng; Liu, Suyi; Su, Guanglei; Fan, Xikang; Chen, Jie; Yuan, Qianting; Xu, Guangfei
Highlights: TCDD exposure promotes liver fibrosis in mice. TCDD induces hepatic stellate cell (HSC) activation. TCDD induces hepatic fibrosis via activating Akt signaling pathways. TCDD stimulates liver inflammation through the Akt/NF-kB p65 signaling pathway. Abstract: 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD) is a widespread environmental pollutant that could induce serious toxic effects in both humans and rodents. Some studies suggested that TCDD exposure may facilitate the activation of hepatic stellate cells (HSCs) and liver injury. However, the underlying molecular mechanism by which environmental pollutants promote liver injury remains poorly understood. In the present study, we established an animal model of TCDD exposure by intraperitoneal injection of TCDD in male C57BL/6J mice. As revealed by Sirius red staining and hematoxylin-eosin (H&E) staining evaluation, we found that TCDD-exposed mice showed extensive disruption of liver architecture, including hepatocellular necrosis, inflammatory cell infiltration, and fibrosis. Furthermore, we showed that TCDD up-regulated the expression and secretion of the pro-inflammatory cytokines tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) in a dose-dependent manner in cultured HSCs. The effects of TCDD on cytokine secretion were very likely mediated by protein kinase B/Akt and Nuclear Factor kappa B (NF- κ B) pathways, as indicated by the fact that TCDD markedly increased Akt phosphorylation and nuclear translocation of NF- κ B p65 in HSCs. Furthermore, LY294002, an Akt inhibitor, significantly attenuated TCDD-triggered HSC activation through blocking Akt phosphorylation and NF- κ B activation. These results indicate that HSCs are susceptible to the cytotoxic effects of TCDD and chronic TCDD exposure may contribute to liver fibrosis by activating HSC Akt and NF- κ B signaling pathways.